The Spectral Presence of Business in India's 2019 Election. (December 2019) - Sinha, Aseema; Wyatt, Andrew
Shifts in the balance of India's economy towards private production have re-opened a debate over the role of the business in its polity. Business interests have found new ways to influence the state at different levels and through multiple institutions. This article concentrates on the composition of the 17th Lok Sabha and its porosity towards business (around 28.4% of these MPs have self-reported business careers). A growing of number of 'industrialists' and entrepreneurs have branched out into a legislative career; they complement a fast-emerging group of entrepreneurial politicians, who already use their legislative and institutional location to develop business interests for themselves and their families. We find that the influence and power of business has become diffuse and central at the same time; it seeped into every aspect of the election campaign and voting process: political recruitment, finance, issues, and policies—in tangible and intangible ways. This spectral presence of business is shaping Indian elections, parties, and democracy and in turn consolidating India's economic reforms and pro-business polity.